Importance of program development competencies for agricultural extension agents' performance in process of technology transfer - Tiraieyari, Neda; Idris, Khairuddin; Hamzah, Azimi; Uli, Jegak (Science Publications, 2010)
Problem statement: The movement of technology from lab to the field has been a challenge for agricultural extension agents. In this study researchers focused on program development competencies for agricultural extension agents in process of technology transfer and discuss the importance of these competencies by determining the relationship between these competencies and performance of extension agents. Approach: The study employed stratified random sampling technique. The sample consisted of 210 extension agents in four states of Malaysia. The data were analyzed using descriptive statistics, Pearson correlation and multiple regression analysis. Results: Extension agents perceived themselves competent in developing program planning, program implementation and program evaluation. The findings supported the positive relationship between competencies and extension agents’ performance. Therefore hypothesis of the study was supported. The results of multiple regressions showed program development competencies explained 0.448 of variance of extension agents’ performance. Conclusion/Recommendations: It can be concluded that performance of extension agents is expected to increase if they have program development competencies. Results supported the importance of these competencies for performance of extension agents in process of technology transfer. Hence to keep extension agents competent and to further improve their performance, these competencies must be considered and upgraded. Continuous assessment of extension agents’ competencies and performance is recommended.